The body - friend or foe in dance? A critical reflection on the body through the Norwegian national curriculum renewal of the upper secondary school subject Dance Techniques - Tone Pernille Østern; Rikke Axelsen Sundberg; Rose Martin (Cappelen Damm Akademisk NOASP, 2022)
This article analyses different discursive positionings related to the body that emerged during the process of renewing the curriculum for the subject Dance Techniques, an in-depth study module in year one of the Programme Area for Dance in upper secondary education in Norway. The hearing process of renewing Dance Techniques uncovered deep tensions in how the body is understood and what position it is given within Norwegian dance education. The aim of this article is to locate different discursive positionings related to the concept of body to better understand these tensions. Through a critical discourse analysis, three rounds of consultation drafts and hearing comments are analysed. Theoretical perspectives connected to the bodily turn and the desired body in dance emerge inductively from the analysis. From the analysis it appears that there is a desire to disembody, disengage and desensitize the dancing body in the curriculum renewal process.